Purwarupa Sistem Monitoring dan Otomasi Hidroponik berbasis IoT menggunakan Aplikasi Android - Dwiarga Sholahuddin; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Hydroponics is one of today's modern farming methods that can be done on limited land. Hydroponics is a farming method without using soil as a medium but using water. One of the main factors for the success of hydroponic farming is controlling the conditions of the growing media, in which the growing medium is water. Temperature and pH are parameters that can be controlled to ensure successful farming with the hydroponic method. Currently, the way to control the temperature and pH values of water is usually done by manual monitoring every day. This method is considered very impractical. Therefore, innovation is needed in the field of technology that can monitor and automate the pH value and water temperature. In this research, a prototype system was created that can perform this function using the Internet of Things method assisted by an Android application as output. This system uses ESP8266 as the main processor to measure temperature and pH values and automate pH values using a 12-volt DC pump and 5-volt submersible pump as well as automate temperature values using a DC fan in the hydroponic system. The accuracy of reading the temperature and pH values obtained by the system is quite high, namely 96.58% for the pH sensor and 99.61% for the temperature sensor. The android application that was created can run well and the system prototype was also successful in automating the hydroponic system's pH and water values.